Columbine, 20 years later and beyond: lessons from tragedy - Schildkraut, Jaclyn (Praeger, 2019)
April 20, 1999 -- The Columbine legacy -- We interrupt this program to bring you breaking news -- Police responses, then and now -- Piecing together the past -- Securing our nation's schools -- An outcry for change -- The (failed) firestorm of legislation -- The larger community footprint -- The infamy of the shooters -- Profiling school and mass shooters -- A piece of popular culture history -- Moving beyond the Columbine effect